2007
DOI: 10.1016/j.watres.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a novel Fe–Mn binary oxide adsorbent for effective arsenite removal

Abstract: Adsorbent OxidationArsenite Removal a b s t r a c t Arsenite (As(III)) is more toxic and more difficult to remove from water than arsenate (As(V)).As there is no simple treatment for the efficient removal of As(III), an oxidation step is always necessary to achieve higher removal. However, this leads to a complicated operation and is not cost-effective. To overcome these disadvantage, a novel Fe-Mn binary oxide material which combined the oxidation property of manganese dioxide and the high adsorption features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
235
3
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 568 publications
(268 citation statements)
references
References 35 publications
24
235
3
6
Order By: Relevance
“…Chemical composition analysis (figures not presented) revealed that Fe and Mn were evenly distributed on the surface and the Fe/Mn molar ratio on the surface was in the range of 5.9-6.1, which is very close to the value of 6:1 of the bulk Fe/Mn molar ratio. The material has a high BET specific surface area of 309 m 2 /g with a pore volume of 0.42 cm 3 /g, which is in agreement with previous results [32,34].…”
Section: Properties Of Prepared Fe-mn Binary Oxidesupporting
confidence: 92%
See 1 more Smart Citation
“…Chemical composition analysis (figures not presented) revealed that Fe and Mn were evenly distributed on the surface and the Fe/Mn molar ratio on the surface was in the range of 5.9-6.1, which is very close to the value of 6:1 of the bulk Fe/Mn molar ratio. The material has a high BET specific surface area of 309 m 2 /g with a pore volume of 0.42 cm 3 /g, which is in agreement with previous results [32,34].…”
Section: Properties Of Prepared Fe-mn Binary Oxidesupporting
confidence: 92%
“…9. For the Fe-Mn binary oxide sample, the band at 1625 cm À1 was assigned to the deformation of water molecules and indicated the presence of physisorbed water on the oxides; three peaks at 1123, 1051, and 974 cm À1 could be primarily attributed to the bending vibration of hydroxyl groups of iron (hydr)oxides (Fe-OH) vibration [34].…”
Section: Zeta Potential and Ftir Analysismentioning
confidence: 99%
“…2. 2 × 10 −4 mol/l iron (ferrous or ferric) and 7.7 × 10 −2 g/l RM were added in arsenic water, meanwhile, research done before had shown that Cl anion has little effect on As(V) removal [20]. Arsenic removal efficiency for ferrous based red mud was higher than ferric based red mud (91.7 ± 2.3% compared to 81.2 ± 3.9%) when the initial As(V) concentrations were varied in the range of 0.16-1.4 mg/l.…”
Section: Arsenic Removal By Ferrous-modified Red Mud Un-modified Redmentioning
confidence: 99%
“…E-mail: jhqu@rcees.ac.cn. numerous approaches have been investigated for the development of cheaper and more effective novel composite adsorbents (Oliveira et al, 2004;Gu et al, 2005;Machado et al, 2006;Zhang et al, 2007b). These composite materials deserve particular attention because they combine the properties and advantages of each of their components.…”
Section: Introductionmentioning
confidence: 99%